Digital disruption in hospitality, sustainable hospitality : a global perspective on people, planet, and profit - Thaichon, Park; Dutta, Pushan Kumar; Haghi, A. K.; Dutta, Soumi (Emerald Publishing Limited, 2025)
Digital Disruption in Hospitality, Sustainable Hospitality: A Global Perspective on People, Planet, and Profit offers a revolutionary insight into the future of tourism and hospitality. This groundbreaking work explores the delicate balance between cutting-edge technology and ethical responsibility in one of the world's largest industries. From the bustling streets of India to the serene eco-resorts of Karnataka, this book takes readers on a global journey through the transformative power of digital innovation in hospitality. Discover how social media is reshaping tourist decisions, how blockchain is personalizing guest experiences, and why the metaverse could be the next frontier for luxury travel. But this isn't just about profit - it's about purpose. Delve into crucial discussions on sustainable culinary tourism in Bangladesh, the impact of fintech on customer loyalty, and the potential of telemedicine in addressing social health challenges. Whether the readers are a hospitality professional, policymaker, or conscious traveler, this book provides the insights and strategies needed to navigate the complex landscape of modern tourism. Join us in reimagining an industry where innovation drives success, sustainability ensures longevity, and every stakeholder - from guests to local communities - thrives. The future of hospitality is here, and it's sustainable.
Keywords: Hospitality industry -- Environmental aspects.; Sustainable tourism.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality, sports, leisure and tourism industries.; elektronické knihy; electronic books